2019
DOI: 10.1530/ec-19-0321
|View full text |Cite
|
Sign up to set email alerts
|

MEN1-associated primary hyperparathyroidism in the Spanish Registry: clinical characterictics and surgical outcomes

Abstract: Primary hyperparathyroidism is the most frequent manifestation of multiple endocrine neoplasia type 1 (MEN1) syndrome. Bone and renal complications are common. Surgery is the treatment of choice, but the best timing for surgery is controversial and predictors of persistence and recurrence are not well known. Our study describes the clinical characteristics and the surgical outcomes, after surgery and in the long term, of the patients with MEN1 and primary hyperparathyroidism included in the Spanish Registry of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 27 publications
1
14
0
4
Order By: Relevance
“…Comparison of bone and mineral metabolism-related biochemical parameters, measured before and after PTX, in our two series of PHPT patients confirmed that parathyroid surgery is efficient in restoring the normal PTH secretion and normalizing total calcium and calcium ion levels, as reported by previous studies [22][23][24][25], in association, in our patients, with a significant reduction in urinary excretion of calcium, in both MEN1 PHPT and sPHPT cases. A study by Coutinho et al [23] also showed a post-operative decrease in urinary calcium, but without reaching statistical significance.…”
Section: Discussionsupporting
confidence: 90%
“…Comparison of bone and mineral metabolism-related biochemical parameters, measured before and after PTX, in our two series of PHPT patients confirmed that parathyroid surgery is efficient in restoring the normal PTH secretion and normalizing total calcium and calcium ion levels, as reported by previous studies [22][23][24][25], in association, in our patients, with a significant reduction in urinary excretion of calcium, in both MEN1 PHPT and sPHPT cases. A study by Coutinho et al [23] also showed a post-operative decrease in urinary calcium, but without reaching statistical significance.…”
Section: Discussionsupporting
confidence: 90%
“…Although it is not closely related to mortality, it is responsible for morbidity, as bone and renal complications are common. Patients may be asymptomatic and diagnosed with HPT due to incidental finding of elevated serum calcium or parathormone levels, but nephrolithiasis, renal colic, or even renal failure may be present at onset [110,115,116]. The same signs and symptoms related to sporadic chronic hypercalcemia are also present in MEN1 patients, and there is increased bone resorption and fracture risk.…”
Section: Gep-net Associated To Men1 and Bone Healthmentioning
confidence: 99%
“…A study performed in the Russian population shows that skeletal complications arise in 87% of patients with sporadic hyperparathyroidism [13]. In PHPT/MEN1, bone mineral density is decreased in 58-72% of the cases [5,14]. The clinical course of bone disease in PHPT/MEN1 patients differs from that in sporadic PHPT/MEN1.…”
Section: Menin In the Development Of Bone Disorders In Men1 Patientsmentioning
confidence: 99%
“…A study performed in the Russian population shows that skeletal complications arise in 87% of patients with sporadic hyperparathyroidism ( 13 ). In PHPT/MEN1, BMD is decreased in 58–72% of the cases ( 5 , 14 ).…”
Section: Menin In the Development Of Bone Disorders In Men1 Patientsmentioning
confidence: 99%